Pedagogia wstydu - refleksja filozoficzna - Boużyk, Maria (Studia Theologica Varsaviensia, 2017)
The article addresses the problem of legitimacy and form of a pedagogy of shame. It consists of two parts. Part I is concerned with the ontological dimension of shame and Part II deals with the education of shame as an important part of the development of human character. Shame is interpreted as a spontaneous protection of human dignity: it is an affectionate signal to identify the value of the external parts of the human personal being (as corporeality and sexuality) only in relation to the value of its inner (spiritual) part. A human being is a unity of body and soul. The value of body is brought by this unity. The experience of shame dignity and, as such, can be strengthened through the acquisition of moral competences that integrate the human realm of emotionality and mentality.